Vision Problems of Children with Individualized Education Programs. - Walline, Jeffrey J.; Johnson Carder, Erica D. (Journal of Behavioral Optometry, 2012)
Background: Much of learning is associated with visual cues, so children with vision-related problems may find it difficult to keep up with their peers in an academic setting. In order to assess the relationship between success in an academic setting and vision-related problems, we compared the prevalence of vision-related problems between children with Individualized Education Programs (IEPs) to population-based samples from the literature. Methods: Eye care professionals completed refraction and cover test on children with an IEP. The prevalence of a variety of conditions exhibited by children with IEPs was compared to prevalence rates reported in the literature. Prevalence rates were compared using Chi-square tests, adjusted for multiple comparisons. Results: Data were analyzed for 255 children reported to have an IEP. The average age of the children was 9.6 ± 2.9 years, and the average spherical equivalent refractive error in the right eye was +0.54 ± 2.21 D. Higher prevalence rates were reported for IEP patients than for samples from the literature for myopia (9 of 13 studies), hyperopia (10 of 13 studies), astigmatism (6 of 9 studies), anisometropia (3 of 4 studies), and strabismus (6 of 6 studies). The entering distance visual acuity of IEP patients was 20/40 or worse for 23.7% of eyes, but 7.2% of eyes still had acuity worse than 20/40 after refraction. Of the children who required some form of treatment, 124 (69.3%) had better than 20/40 entrance visual acuity in both eyes. Conclusion: Children with IEPs have a significantly higher prevalence of myopia, hyperopia, astigmatism, anisometropia, and strabismus than most population-based samples in the literature. Many of these vision problems would be undetected by vision screenings based on distance visual acuity, illustrating the need for comprehensive vision examinations for children who are struggling academically.